2007
DOI: 10.1245/s10434-006-9290-7
|View full text |Cite
|
Sign up to set email alerts
|

Heme Oxygenase-1 Gene Promoter Polymorphism is Associated with Risk of Gastric Adenocarcinoma and Lymphovascular Tumor Invasion

Abstract: These findings suggest that the long (GT)n repeat of HO-1 gene promoter was associated with a higher frequency of gastric adenocarcinoma, and the medium (GT)n repeat might possess protective effect against gastric adenocarcinoma with a lower frequency of lymphovascular invasion in tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…It has also demonstrated that SS genotype could cause increasing of metastatic activity risk of gastric cancer. Against our results, Lo and coworkers demonstrated that L allele is associated with risk of gastric cancer [19]. Also, studies of Dicken et al [4] on cardiovascular patients, Yamada et al [34] on emphysema, Wu et al [33] on carotid atherosclerosis, Schillinger et al [25]) on abdominal aortic aneurysm, and Chang et al [2] on squamous cell carcinoma showed that L allele has an association with those diseases.…”
Section: Discussionsupporting
confidence: 61%
“…It has also demonstrated that SS genotype could cause increasing of metastatic activity risk of gastric cancer. Against our results, Lo and coworkers demonstrated that L allele is associated with risk of gastric cancer [19]. Also, studies of Dicken et al [4] on cardiovascular patients, Yamada et al [34] on emphysema, Wu et al [33] on carotid atherosclerosis, Schillinger et al [25]) on abdominal aortic aneurysm, and Chang et al [2] on squamous cell carcinoma showed that L allele has an association with those diseases.…”
Section: Discussionsupporting
confidence: 61%
“…An association with functional polymorphisms of the HO-1 gene and clinical outcome parameters has also been found in other pathological conditions, such as pulmonary emphysema, certain cardiovascular diseases and malignancies (14,19,(30)(31)(32)(33)(34)(35). With respect to transplantation, two groups have previously reported an association between HO-1 polymorphism in the donor and outcome after kidney transplantation (21,22).…”
Section: Discussionmentioning
confidence: 89%
“…A GT length-promoter polymorphism for HO-1 has been described that controls the level of HO-1 expression and has been shown to be highly correlative with severity of disease, including cancer (27). Individuals with a long (GT)n repeat, which is associated with low expression levels of HO-1, showed a higher frequency of gastric or lung adenocarcinoma (28) and oral squamous cancer (29) than individuals with short GT repeats and higher HO-1 expression. Additionally, application of CO via a CO-releasing molecule provided a significant inhibition in photocarcinogenesis in mice (30).…”
Section: Discussionmentioning
confidence: 99%